Formation of ecological culture - Bernotas, Vytautas (Acta Paedagogica Vilnensia, 1998)
Ecological education plays an important part in the formation of pupils' ecological culture. It stimulates pupils' wish to protect nature, to take care of it and love it. The formation of pupils' ecological culture is carried out integrally, through lessons in various subjects, extra-curricular activities and regional studies. The paper deals with problems of formation of ecological culture and its sources. The concept of ecological education, its aims, tasks, components, content, forms and methods are revealed. A programme of pupils' ecological education is presented, and pedagogical conditions of successful ecological education are established.
Keywords: school; students; ecological education; ecological culture; teaching methods